An Analysis of the Implementation of an Accounting Information System for Inpatient Services in Enhancing the Effectiveness of Hospital Revenue Internal Control: A Case Study of Setiabudi Hospital - Dahyuni Lbs; Waizul Qarni; Yenni Samri Juliati Nasution (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the implementation of an Accounting Information System (AIS) in inpatient service operations to enhance the effectiveness of internal revenue control at Setiabudi Hospital Medan. This research employed a qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the implementation of an integrated AIS through the Electronic Medical Record (EMR) system has improved operational efficiency, accuracy and reliability of transaction recording, and accelerated administrative and financial reporting processes. Furthermore, the system supports the effectiveness of internal control through segregation of duties, transaction authorization, and continuous monitoring. The study concludes that the implementation of the accounting information system at Setiabudi Hospital Medan has been effectively carried out and plays a significant role in enhancing the hospital's internal revenue control